Normative Juridical Review Regarding Bank Interest in Islamic Law - Lumban Gaol, Christopher Panal (PT. Riset Press International, 2023)
This journal aims to examine the concept of bank interest (riba) within the framework of Islamic law (Sharia). The practice of charging and receiving interest has been a topic of significant debate and controversy among Islamic scholars and jurists. This paper provides an in-depth analysis of the philosophical underpinnings of bank interest in Islamic law, taking into account various perspectives and interpretations within the Islamic legal tradition. The journal begins by exploring the foundational principles of Islamic law and its ethical framework, highlighting the prohibition of riba as outlined in the Quran and the Hadith. It discusses the historical context and evolution of Islamic banking and finance, emphasizing the need for alternative financial mechanisms that comply with Islamic principles. The study then delves into the philosophical considerations surrounding bank interest from an Islamic legal perspective. It examines different schools of thought and the rationale behind their positions, including the arguments for and against the permissibility of bank interest. The utilitarian perspective evaluates the societal consequences of interest-based transactions, while the deontological approach emphasizes the adherence to moral principles. The contractualist viewpoint focuses on the voluntary agreements between parties, and the concept of justice and equality is examined in relation to interest-based transactions. Furthermore, the journal analyzes contemporary practices in Islamic banking and finance, including the development of Islamic financial instruments that adhere to Sharia principles. It explores the role of regulatory bodies in overseeing and ensuring compliance with Islamic law in the financial industry. The research concludes by synthesizing the diverse perspectives and providing a comprehensive understanding of the philosophical considerations surrounding bank interest in Islamic law. It emphasizes the importance of contextual interpretation and critical analysis within the Islamic legal tradition to address the challenges and complexities posed by modern financial systems.